The Effect of Mobile Legend Game on Vocabulary Mastery of the Tenth Grade Student of SMAN 1 Cluring - Arik Diantoro; Tri Mulyati; Abdul Halim (LUNAR, 2020)
Vocabulary is one basic component to be mastered. It is reasonably, remembering that the four language skills need knowledge of words because they will get nothing without vocabulary. The large the students master vocabulary the better they perform their language. This study is to measure whether there is a significant effect of Mobile Legends Game on the students’ vocabulary mastery the researcher used experimental design. The research was conducted at SMAN 1 Cluring from 1st August until 31thAugust 2018, in the academic year 2018/2019. The population of the research was Tenth grade students at SMAN 1 Cluring. They were 31 students as respondents of the research and taken by using cluster random sampling. The sample was X IPA 1 as the experimental class. The total numbers of the respondents were 31 students. The technique of collecting data was giving a test. The tests used in this research is vocabulary test in the form of multiple choice. The data was analyzed by using t-test formula. Based on the result of the data analysis of T-test formula, it can be known that the result of t- test is higher than the t table. That is 7,833 > 2,048. The degree of freedom in the level significant is 30 the valuable of ttable is 2.048 from the analysis. It shows that “There is a significant effect of Mobile Legend Game on the vocabulary mastery of the tenth grade students at SMAN 1 Cluring in the 2018/2019 Academic year. Based on the result, the English teachers could use Mobile Legends as the alternative teaching media to make students Vocabulary mastery. Further, students are suggested to use Mobile Legends to increase their vocabulary.